Webbing Egypt: an ethnographic insight into levels of imagination surrounding the production of web sites - Panovic, Ivan (AUC Knowledge Fountain, 2001)
This thesis is an ethnographic description of practices of the producers of Egypt-based and Egypt-related websites.